I have a output signal $Y(t)= \sum_{n=-\infty}^{\infty} Z_n \delta (t-n\tau) h(t)$ and $Z_n$ is a random variable with equal probability to be $+-1$ and h(t) is $sinc(\frac t {\tau})$

and the Expected value of $Y(t)$ is

$E(Y(t)) = E[\sum_{n=-\infty}^{\infty} Z_n \delta (t-n\tau) h(t)]$

$=\sum_{n=-\infty}^{\infty}h(n\tau) E[Z_n]$


But if I calculated in other way

$\int_{-\infty}^\infty t Y(t) dt$

$=\int_{-\infty}^\infty t \sum_{n=-\infty}^{\infty} Z_n \delta (t-n\tau) h(t) dt$

$= \int_{-\infty}^\infty \sum_{n=-\infty}^{\infty} tZ_n \delta (t-n\tau) h(t) dt$

$= \int_{-\infty}^\infty \sum_{n=-\infty}^{\infty} n\tau Z_n h(n\tau) dt$

$= \sum_{n=-\infty}^{\infty} [n\tau h(n\tau)\int_{-\infty}^\infty Z_n dt]$

Why I have two different result with same signal? Thanks for any help.

  • $\begingroup$ To the Dilip's Question: Actually, This is a tutorial question from my class. The original setting is convolution between $\delta(t-n\tau) and h(t)$, as @Dilip say. I just curious why I can have two different set of solution when I time two signal together. Now I know this is because the second one is calculated the joint probability. Thanks Ixop and Dilip. $\endgroup$ – Samuel Mar 19 '13 at 6:49
  • $\begingroup$ So it is a convolution as my answer suggested, and so what $Y(t)$ works out to be is $$Y(t) = \sum_{n=-\infty}^{\infty} Z_n h(t-n\tau) = \sum_{n=-\infty}^{\infty} Z_n\operatorname{sinc}\left(\frac{t-n\tau}{\tau}\right).$$ In other words, both of the calculations you present in your question are nonsensical since you are not even looking at the correct $Y(t)$, and the fact that the two calculations give different answers is really not of much interest. $\endgroup$ – Dilip Sarwate Mar 19 '13 at 16:53

Your second equation $E[Y(t)] = \int_{-\infty}^\infty tY(t)dt$ is wrong; that won't calculate the expected value of $Y(t)$. The equation you are thinking of is $E[Y(t)] = \int_\Omega Y(t)P[Y(t)]$, where you would determine $P[Y(t)]$ by a joint probability of the $Z_n$'s. That's why they don't match.

In any case, @Dilip-Sarwate has an answer showing that you can simplify this particular equation to a state where the answer becomes trivial (and is equal to the first answer you found).


If $h(t)$ is continuous at $a$, then $h(t)\delta(t-a) = h(a)\delta(t-a)$. Since the $\operatorname{sinc}$ function is continuous everywhere, $$\begin{align} Y(t) &= \sum_{n=-\infty}^{\infty} Z_n\delta(t-n\tau)h(t)\\ &= \sum_{n=-\infty}^{\infty} Z_n\delta(t-n\tau)h(n\tau)\\ &= \sum_{n=-\infty}^{\infty} Z_n\delta(t-n\tau)\operatorname{sinc}(n)\\ &= Z_0\delta(t) \end{align}$$ since $\operatorname{sinc}(n) = \begin{cases}1,&n = 0,\\0,& n\neq 0.\end{cases}$ You (or your textbook's authors) probably meant to write something else. You sure you are not missing a $\star$ indicating a convolution between that $\delta(t-n\tau)$ and $h(t)$?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.